This book stinks! : gross garbage, rotten rubbish, and the science of trash - Flynn, Sarah Wassner (National Geographic kids., 2017)
Get up close and personal with a wonderful world of waste. From composting and recycling, to landfills and dumps, to how creative people are finding new ways to reuse rubbish. It's fun to talk trash when it's jam-packed with infographics, thematic spreads, photos, sidebars, stats, and facts. Also included are quizzes and activities to inspire kids to take action, be proactive, and rethink the things we throw away.